The festival dedicated to the anniversary of the vision of Agia Pelagia and other rituals - Haland, Evy Johanne (Traditiones (Ljubljana), 2012)
The local festival dedicated to the Anniversary of the Vision of Agia (Saint) Pelagia or Osia (Venerable, Blessed, Saint)1 Pelagia is celebrated on the Greek island of Tinos and is dedicated to one of the most recent Orthodox saints, Saint Pelagia, a nun that was sanctified in 1971. After the great Greek War of Liberation (1821) broke out, the pious nun Pelagia had several mystical visions that lead to the discovery of the miraculous icon of the Annunciation.
Keywords: ethnology; Religija; religion; Svetniki; Pravoslavje; customs; celebrations; Grčija; Greece; Etnologija; Šege; Verski prazniki; Mitologija; mythology; Legende; ljudski prazniki